Numerical and wind tunnel investigation of Hot Air Recirculation across Liquefied Natural Gas Air Cooled Heat Exchangers. Issue 172 (January 2018) - Ghani, Saud; Gamaledin, Seifelislam Mahmoud Ahmad; Bakochristou, Foteini; El-Bialy, Esmail; Mohamed, Mohamed Mostafa; Elsawi, Rodina Mohamed El Hassan
Abstract: Air Cooled Heat Exchangers (ACHE)s are used for heat rejection in Liquefied Natural Gas (LNG) plants. Their thermal performance decreases under elevated ambient temperatures and windy conditions as exhaust air recirculates back into the ACHE units causing Hot Air Recirculation (HAR). This paper investigates the effect of various incident wind speed and directions on HAR. Understanding HAR helps to avoid undesirable work conditions. Three dimensional Computational Fluid Dynamics (CFD) studies were utilized to simulate the airflow around a full scale LNG plant. The simulations clearly captured HAR between parallel ACHE banks (Cross-HAR) and within a single ACHE unit (Self-HAR). Wind tunnel smoke visualization was used to qualitatively assess the CFD model. The impact of removing downstream ACHE protection screens on the HAR was computationally investigated showing an exhaust air temperature reduction of 5 °C. Different HAR mitigation methods were proposed using different configurations of side winglets. Horizontal winglets were shown to be more effective than vertical winglets as they decreased intake and exhaust air temperatures by about 5 °C and 8 °C respectively and increased exhaust air velocity by 1.2 m/s. This work provides a thorough understanding of HAR around ACHEs and proposes mitigation methods to reduce its effects on plant production. Highlights: HAR is sensitive to incident wind speed and direction. The pressure drop downstream the ACHE bank has a role in developing HAR. Horizontal winglets are better mitigation method than the vertical winglets. Weather data and plant geometry are required for effective design of ACHE banks. CFD and wind tunnel testing are useful tools to design optimized ACHE units.